ANALYSIS OF WRITTEN LANGUAGE PRODUCTION IN THE CHILD WITH DYSGRAPHIA - Khotijah, Siti (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
This research is focused on exploring in-depth the production of written language and the role of parents in a child with dysgraphia using the psycholinguistic assessment of language (Caplan, 1992). The research used a qualitative approach with a case study method. This approach is used to explore a person who has dysgraphia. The data collection techniques used are observation and interviews. The participant in the research is a grade IV elementary school student with the initials WH who is indicated to have dysgraphia. The data analysis techniques include data reduction, data display, and conclusion drawing (Miles & Huberman, 1994). The results of the study show that the role of parents in training and guiding their children to write can have a significant influence on the production of written language in a child with dysgraphia. The more often parents do activities that can train the child to write, the more likely it is that the child will recover from dysgraphia.